THEORETICAL FOUNDATIONS OF ECONOMIC TERMINOLOGY AND TRANSLATION (Modern education and development, 2025)
This article provides a detailed overview of economic terminology, emphasizing its specialized nature and essential role in conveying economic knowledge across various fields, including academia, policy, business, and international communication. It explores how economic terms evolve alongside developments in the global economy and discusses the contextual, linguistic, and cognitive aspects of terminology variation. The article also addresses the complexity of translating economic texts, highlighting the importance of applying appropriate translation theories—especially the principle of equivalence—and the necessity of standardization in economic translation practices. Through referencing key scholars like Nida and Catford, the paper underscores the importance of accurate and context-sensitive translation for ensuring clarity and consistency in multilingual economic discourse.